2019
DOI: 10.1093/conphys/coz002
|View full text |Cite
|
Sign up to set email alerts
|

Artificial light at night disturbs the activity and energy allocation of the common toad during the breeding period

Abstract: Artificial nocturnal lighting, a worldwide phenomenon that is currently expanding, experimentally reduces the duration of activity and increases oxygen consumption at rest of the common toad, a nocturnal amphibian. These behavioural and physiological changes could be associated with an increase in individual stress levels and thus affect toad populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 38 publications
0
23
0
4
Order By: Relevance
“…Few reviews on ALAN effects on amphibians are available [70][71][72], and several recent studies investigated the effects of ALAN on amphibians. ALAN decreased metamorphic duration and juvenile growth in American toads (Anaxyrus americanus) [73], and reduced activity and altered energy allocation in common toads (Bufo bufo) [74]. Furthermore, a shift and shortening of the calling season of male Brazilian anurans was measured in a light-polluted wetland as compared to a similar site without light pollution [75].…”
Section: Amphibiansmentioning
confidence: 91%
“…Few reviews on ALAN effects on amphibians are available [70][71][72], and several recent studies investigated the effects of ALAN on amphibians. ALAN decreased metamorphic duration and juvenile growth in American toads (Anaxyrus americanus) [73], and reduced activity and altered energy allocation in common toads (Bufo bufo) [74]. Furthermore, a shift and shortening of the calling season of male Brazilian anurans was measured in a light-polluted wetland as compared to a similar site without light pollution [75].…”
Section: Amphibiansmentioning
confidence: 91%
“…The diel distribution of feeding bouts was altered in mice, resulting in obese individuals (Fonken et al, 2010), while activity and metabolism were uncoupled in amphibians exposed to light at night (Touzot et al, 2019). These lab studies highlight the need for analysing to- (Somanathan, Borges, Warrant, & Kelber, 2008), or the selection of food sources (Kelber, Balkenius, & Warrant, 2002) or mates (Gomez et al, 2009).…”
Section: A Pred I C Tive B I Og Eog R Aphi C Al Fr Ame Work For Al mentioning
confidence: 93%
“…The diel distribution of feeding bouts was altered in mice, resulting in obese individuals (Fonken et al, 2010), while activity and metabolism were uncoupled in amphibians exposed to light at night (Touzot et al, 2019). These lab studies highlight the need for analysing together activity and metabolic budgets or relevant proxies when other physiological measurements cannot be made.…”
Section: A Pred I C Tive B I Og Eog R Aphi C Al Fr Ame Work For Al mentioning
confidence: 94%
“…Several mechanistic links between elevated light levels and disruptions to critical ecological processes (Gaston et al 2013) such as pollination (Knop et al 2017), migration (Cabrera‐Cruz et al 2018), herbivory (Bennie et al 2015), habitat connectivity (Bliss‐Ketchum et al 2016) and changes to community structure (Sanders and Gaston 2018) have been demonstrated. At the organismal level, documented impacts of elevated nightlight include increased physiological stress (Ouyang et al 2017), mismatched biological timing (Gaston et al 2017), decreased reproduction (Touzot et al 2019), as well as changes to predation risk (Brown et al 1988), movement patterns (Degen et al 2016) and vigilance time (Yorzinski et al 2015). However, impacts on species have mostly been documented at relatively small scales (e.g.…”
Section: Introductionmentioning
confidence: 99%